2008
DOI: 10.1016/j.neuroscience.2008.08.064
|View full text |Cite
|
Sign up to set email alerts
|

Time course of morphine's effects on adult hippocampal subgranular zone reveals preferential inhibition of cells in S phase of the cell cycle and a subpopulation of immature neurons

Abstract: Opiates, such as morphine, decrease neurogenesis in the adult hippocampal subgranular zone (SGZ), raising the possibility that decreased neurogenesis contributes to opiate-induced cognitive deficits. However, there is an incomplete understanding of how alterations in cell cycle progression and progenitor maturation contribute to this decrease. The present study examined how morphine regulates progenitor cell cycle, cell death and immature SGZ neurons (Experiment 1) as well as the progression of SGZ progenitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 69 publications
3
69
1
Order By: Relevance
“…Although nestin-GFP mice have been used to determine the neurogenic stage affected by stimuli like running or drugs of abuse (e.g., 9, 31), the current data reveal how stress affects different stages of dentate gyrus neurogenesis. Because the populations of stem-like Type-1 and mature progenitor Type-3 cells appear to be largely unaffected by chronic stress, our data are consistent with previous work that manipulation of the rapidly dividing Type-2 population is a prime and robust way to modulate neurogenesis (9,31).…”
Section: Discussionsupporting
confidence: 90%
“…Although nestin-GFP mice have been used to determine the neurogenic stage affected by stimuli like running or drugs of abuse (e.g., 9, 31), the current data reveal how stress affects different stages of dentate gyrus neurogenesis. Because the populations of stem-like Type-1 and mature progenitor Type-3 cells appear to be largely unaffected by chronic stress, our data are consistent with previous work that manipulation of the rapidly dividing Type-2 population is a prime and robust way to modulate neurogenesis (9,31).…”
Section: Discussionsupporting
confidence: 90%
“…An opioid-induced attenuation of neurogenesis in hippocampus was earlier seen in male rats exposed to morphine (Eisch et al, 2000). Thus, opiates, such as morphine, is seen to reduce neurogenesis in the adult hippocampal subgranular zone (SGZ), suggesting that a waning neurogenesis contributes to opioidinduced deficits in cognitive function (Arguello et al, 2008). Enhanced apoptosis following exposure to opioids was reported to involve an upregulation of the proapoptotic caspase-3 and Bax proteins following NMDA receptor activation (Mao et al, 2002).…”
Section: Opioid-induced Adverse Effects On Cognitive Functionsmentioning
confidence: 99%
“…These observations suggest that the opioid regulation of neurogenesis in the adult rat hippocampus may be mediated by direct effects of the opioid drugs on the hippocampal function. The recent study by Arguello and co-workers, as mentioned above, demonstrated that chronic morphine attenuates neurogenesis in the SGZ by impeding cell-dividing, primarily in the S-phase, and inhibiting progenitor cell progression to a more mature stage (Arguello et al, 2008). In order to find strategies to reverse the opioid-induced damage to the hippocampal function it is essential to look for agents that may stimulate hippocampal progenitors and thereby increase neurogenesis and regeneration of nerve cells.…”
Section: Attempts To Reverse Of Opioid-induced Impairments On Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurogenesis includes distinct stages, such as cell proliferation, neuronal differentiation, and survival, that can be influenced by various environmental features. For example, morphine implantation decreases the proliferation of cells in the hippocampus DG (7). In one study, buprenorphine used as an opiate analgesic decreased the number of proliferating cells (8).…”
Section: Introductionmentioning
confidence: 99%